MONET: a database for prediction of neoantigens derived from microsatellite loci - Deng, Nan; Sinha, Krishna M.; Vilar, Eduardo (Frontiers in Immunology, 2024)
The MicrOsatellite NEoantigen Discovery Tool (MONET) is a comprehensive database that enable researchers to quickly access potential tumor mutated neoantigens (neoAgs) within coding microsatellite sequences. MONET houses a range of predicted mutated neoAgs derived from microsatellites tracts present in the human reference genome. In addition, it provides detailed annotation of these neoAgs by providing key features including binding affinity, stability, expression, frequency, and potential pathogenicity of mutations from which they are derived. These annotations are generated using popular algorithms, tools, and major public databases. MONET provides a user-friendly web interface (https://monet.mdanderson.org) to facilitate the exploration of neoAgs from candidate target genes and the top possible neoAgs for specific MHC alleles.